An efficient and metal free synthesis of benzylpyridines using HI through the deoxygenation reaction1. Issue 72 (6th August 2015) - Chandrasekar, Selvaraj; Karthikeyan, Iyyanar; Sekar, Govindasamy
<x xml:space="preserve">Abstract</x> An efficient and practical method for the synthesis of benzylpyridines has been developed using aqueous hydroiodic acid in acetic acid.